(untitled) (American International Journal of Sciences and Engineering Research, 2019)
This literature review concerned with antipyrine compound . Antipyrine compound is very important compound in many chemistry fields such as in coordination chemistry , analytical chemistry as a reagent which continuously identified for possible uses and applications in several fields beside to pharmacological , medical and industrial fields.